Survey, collection and characterization of Indian avocado (Persea americana) germplasm for morphological characters - M, MURALIDHARA B; T, SAKTHIVEL; G, KARUNAKARAN; R, VENUGOPALAN; V, VENKATRAVANAPPA; SAVADI, SIDDANNA; S, KARTHIK NAYAKA V; S, SHIVASHANKARA K; K, HONNABYRAIAH M (The Indian Journal of Agricultural Sciences, 2023)
Avocado (Persea americana Mill.) is emerging as one of the high-valued fruit crops in India. Recently, demand for avocados is increasing due to the high nutritional value of the fruits. Currently, avocados are not grown on large commercial scale and there is a need of good high yielding varieties for commercial cultivation. Hence knowledge on genetic diversity of avocado is essential for selection of superior genotypes. Currently, the information on genetic diversity of Indian avocados is limited. Therefore, an intensive survey was carried out in major avocado growing areas of India to collect 83 diverse accessions. The collected accessions were characterized for 27 characters using IPGRI, avocado descriptors. Among the characters studied, 2 characters were dimorphic and remaining 25 were polymorphic. The maximum accessions showed the presence of rough trunk surface (48.19%), oval leaf shape (44.58%), acute leaf base (86.75%) and leaf apex (72.29%). The dominance of light green fruit colour (38.55%) with smooth peel surface (54.22%) was noticed. The wide variability for pulp and seed characters was also documented. The principal component analysis and cluster analysis showed the existence of wider variability among the collected accessions. The existence of huge diversity helps to conserve trait specific accessions and varietal improvement through selections and hybridizations.